A study on the factors that influence employee motivation at cabinet unit, Prime Minister Department / Nurul Atiqah Hamid and Nurul Hanis Mohd Radzuan - Hamid, Nurul Atiqah; Mohd Radzuan, Nurul Hanis (Faculty of Administrative Science and Policy Studies, 2013)
This research is about the factors that influence employee motivation at Cabinet Unit, Prime Minister Department. The purpose of this research is to determine whether there is any relationship between task identity and employee motivation, to determine whether there is any relationship between job autonomy and employee motivation, to identify whether there is any relationship between task significant and employee motivation and lastly to identify the factor that influences employee motivation the most at Cabinet Unit, Prime Minister Department. Based on this research, there are three factors that influence to employee motivation which are task identity, job autonomy and task significant. This research represents motivation in Cabinet Unit, Prime Minister Department. Only 97 respondents were selected using simple random sampling out of 125 employees. Based on this research, task identity shows the most significant relation which means task identity factors that influence the most on employee motivation in Cabinet Unit, Prime Minister Department.